Construction and validation of a supervisory effectiveness scale - Ayson, Elmila B. (1982)
The aim of the research is to explore the area that relates to supervisory effectiveness. It aims at constructing an inventory, the Supervisory Effectiveness Scale, that will bring out the factors that contribute to supervisory effectiveness. It aims to validate the constructed scale against the on-the-job performance and ratings of subordinates.
Thesis (D.Ed.)--University of the Philippines, Quezon City.
Keywords: Supervisors, Rating of; Supervision of employees